The safety and efficacy of third- and fourth-generation cryoballoons for atrial fibrillation: a systematic review and meta-analysis - Zhang, Man-Li; Zhang, Chao; Peng, Jian-Yong; Xing, Shu-Qiao; Guo, Jian; Wei, Chen-Long; Zhang, Neng-Fang; Ma, En; Chen, Wen-Sheng (Frontiers in Cardiovascular Medicine, 2024)
Objectives An increasing number of studies have shown that third (CB3)- and fourth-generation cryoballoons (CB4) have been used to treat various types of atrial fibrillation (AF), but previous research regarding the safety and efficacy of CB3 or CB4 ablation remains controversial. Therefore, a meta-analysis was performed to further evaluate the safety and efficacy of pulmonary vein isolation (PVI) using the CB3 and CB4 in the treatment of AF. Methods We searched PubMed, the Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, China Science and Technology Journal Database, and Clinicaltrials.gov up to December 2023 for qualified trials and data extraction according to inclusion and exclusion criteria. All analyses were carried out using Review Manager 5.3 software. Results The meta-analysis included 13 observational studies consisting of 3,281 subjects and did not include a randomized controlled trial. Overall analyses indicated that the CB3 significantly reduced total procedure time [weighted mean difference (WMD) = −8.69 min, 95% confidence interval (CI) = −15.45 to −1.94 min, I2 = 93%], increased the PVI recording [relative risk (RR) = 1.24, 95% CI = 1.03–1.49, I2 = 90%], and increased the mean nadir temperature of overall PVs (WMD = 2.80°C, 95% CI = 1.08–4.51°C, I2 = 89%) compared with the CB2. Moreover, the CB4 significantly reduced the total procedure time (WMD = −14.50 min, 95% CI = −20.89 to −8.11 min, I2 = 95%), reduced the fluoroscopy time (WMD = −2.37 min, 95% CI = −4.28 to −0.46 min, I2 = 95%), increased the PVI recording (RR = 1.40, 95% CI = 1.15–1.71, I2 = 90%) compared with the CB2. Time-to-isolation, the success rate of PVI, AF recurrence, and complications in the CB3 and CB4 were not significantly different compared with the CB2. Conclusion These findings demonstrated that the CB3 and CB4 tended to be more effective than the CB2 in the treatment of AF, with shorter procedure times, more PVI recording, and similar safety endpoints.